FINANCIAL MANAGEMENT BEHAVIOR: HUBUNGAN ANTARA SELF-EFFICACY, SELF-CONTROL, DAN COMPULSIVE BUYING - Hikmah, Mukhibatul; Worokinasih, Saparila; Rut Damayanti, Cacik (FIA UB, 2020)
The ability to manage finances potentially affect a person's financial condition and psychological condition in the future. This study aims to determine the impact of self-efficacy and self-control on financial management behavior and its impact on compulsive buying behavior. The study was conducted by collecting and analyzing related journals for the research objectives. Based on literature studies conducted, self-efficacy and self-control affect financial management behavior and compulsive buying. The studies also show that self-efficacy influences self-control, increasing the level of self-efficacy in a person can prevent her/him in compulsive actions such as compulsive buying.